Wear surface damage of a Stainless Steel EN 3358 aeronautical component subjected to sliding (Fracture and Structural Integrity, 2012)
The present paper describes the failure analysis of an aircraft component subjected to several episodes of in service failure, resulted in loss of the aircraft safety. Modern aircrafts are provided with mechanical systems which have the task to open not pressurized hatches during landing. The components of such systems are subject to considerable mechanical stresses in harsh environment (presence of moisture and pollutants, significant and sudden temperature variations). The system is constituted by a sliding piston, a related nipple and by a locking system consisting of 4 steel spheres which are forced into a countersink machined on the piston when the hatches is open. The whole system is activated by a preloaded spring. The machined parts, nipple and piston, are made of EN3358 steel (X3CrNiMo13-8-2), a precipitation hardening stainless steel with very low content of carbon often used in the aerospace. The samples provided by the manufacturer present different types of damage all referable to phenomena relative to the sliding of the piston inside the nipple. The present paper describes the different damage observed and the microstructure of the material, then are reported the results obtained from the characterization of the material of the samples by means of optical and electronic microscopy, carried out to define the mechanisms involved in the system seizure. In order to define the primary cause of failure and to propose solutions to be adopted, also analyzing the criticality of using this PH stainless steel for this application, the results of different tests were compared with system design and working data.
Keywords: Wear